Про алгоритми визначення станів рівноваги відкритої економічної системи за наявності монополістів - Makhort, Andrii P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2016)
There is an open economy created by insatiable consumers. The part of consumers can product own goods. The equilibrium principles are of a Walrasian type. The model uses the approach of an economy with regular interests of consumers. There is an algorithm for solving the equilibrium problem. The algorithm takes into account a possibility of consumers interests of subjects of the economy depended on additional characteristics. Obtained limitations of model characteristics of the economy prove an equilibrium existence. The characteristics of discovered equilibrium states belong to a defined area of values. The relation between a selection of a taxation strategy and the realization of a particular equilibrium state is indicated.